Innovative materials and design for sustainable transportation infrastructure : selected papers from the International Symposium on Systematic Approaches to Environmental Sustainability in Transportation, August 2-5, 2015, Fairbanks, Alaska - Zhao, Sheng (Writer on pavements); Liu, Jenny (Civil engineer); Zhang, Xiong, 1971- (American Society of Civil Engineers, 2015)
Selected papers presented at the International Symposium on Systematic Approaches to Environmental Sustainability in Transportation held in Fairbanks, Alaska, August 2-5, 2015. Sponsored by the Construction Institute of ASCE. Innovative Materials and Design for Sustainable Transportation Infrastructure contains 37 peer-reviewed papers on innovations and advances in sustainable pavement materials. Topics include: asphalt and concrete pavement; recycled and reusable materials; geo-materials; soil stabilization; ground improvement; and sustainable design in underground spaces. This collection will be of interest to practitioners and researchers in transportation and infrastructure construction.
Keywords: Transportation engineering -- Congresses.; Sustainable engineering -- Congresses.; elektronické knihy; electronic books